ANALISIS PENGARUH MANAJEMEN KUALITAS TOTAL TERHADAP KINERJA UKM DENGAN MEDIASI BUDAYA ORGANISASI PADA SEKTOR PAKAIAN MUSLIM DI TANAH ABANG, JAKARTA PUSAT - Saidah Saidah; Wahyuningsih Santosa; Jennifer Victoria Astari Haryanto (Universitas Nusa Cendana, 2022)
This study aims to examine and analyze of the effect of Total Quality Management on SME’s Performance by mediating of Organizational Culture in Muslim clothing sector in Tanah Abang, Central Jakarta. Data collection methods obtained by distributing questionnaire with a simple random sampling to 125 respondents. The analysis method is Partial Least Square- Structural Equation Modelling (PLS-SEM) using application SmartPLS 3.0. The result of this study showed that in first hypothesis there was a effect of Total Quality Management on SME’s Performance, then in second hypothesis there was a effect of Total Quality Management on Organizational Culture, then in third hypothesis there was a effect of Organizational Culture on SME’s Performance, and next in fourth hypothesis there was a effect of Total Quality Management on SME’s performance by mediating of Organizational Culture. Keywords: Organization Culture, SME’s Performance, Total Quality Management